Studi Kemampuan Daya Tahan Kardiovaskular dan Daya Tahan Otot Tungkai Atlet pada Persatuan Bulutangkis Bungo Sport: Daya Tahan Kardiovaskular; Daya Tahan Otot Tungkai; Badminton - Pratama Hendri, Nabila; Ismi Mori Saputra, Deka; Maulana Putra, Ikhsan; Bani Pilitan, Raja (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Badminton is a sport of small ball games played with rackets and shuttlecocks over a net into the opponent's area. The goal is to hit the shuttlecock so that it falls in the opponent's area and prevent the opponent from doing the same. This study uses a quantitative descriptive research type. The population in this study was 30 players. The sample in this study was 10 athletes with a sampling technique using purposive sampling. The instruments used in this study were tests and measurements to measure physical condition. Data analysis techniques were collected through conversion of physical condition tests and with percentages. The results of this study were obtained based on two components of physical condition after being converted, including: (1) strength in physical condition in wall squats of 9 is in the Very Good category, (2) endurance in physical condition v02max of 9.2 is in the Very Good category. Based on the results of the study, it can be concluded that the physical condition of the Bungo Sport Badminton Association athletes of 4.55 is included in the Sufficient category.